UNETHICAL USE OF ARTIFICIAL INTELLIGENCE AMONG BUSINESS EDUCATION STUDENTS: BEST REGULATORY PRACTICES (NAU Journal of Technology and Vocational Education, 2026)
The rapid integration of Artificial Intelligence (AI) into education has brought about significant advancements, but it has also introduced challenges, particularly regarding the unethical use of AI especially among students. This prompted this study to identify the strategies for regulating unethical use of AI among Business Education students in tertiary institutions in Anambra State.  Four research questions guided the study. The study adopted a descriptive survey research design. The population comprised 135 final year (2023/2024 session) students of Business Education in public Universities in Anambra state. Census Survey sampling technique was adopted; therefore, the entire population were studied. A structured questionnaire of 22 items was developed by the researchers and used to collect data. The questionnaire was validated by three experts. The questionnaire was subjected to trial testing to determine the internal consistency of the instrument. An overall co-efficient value of 0.79 using Cronbach Alpha Method was obtained. Mean and standard deviation were used to answer the four research questions. Findings revealed that awareness, teacher-training, and consequences influences Business Education students’ decisions to use AI ethically. Based on the findings, the researchers recommended that school management should promote AI awareness initiatives, such as seminars and workshops, to educate Business Education students on the ethical implications of AI technologies and how to use them responsibly. It was also recommended that academic institutions should establish clear penalties for unethical AI usage, enforcing them consistently to foster responsible AI behavior among students.
Keywords: Artificial Intelligence; Regulation; Unethical Usage; Business Education Students; Strategies